1995
DOI: 10.1002/j.1460-2075.1995.tb00052.x
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of translation initiation factor eIF-2 phosphorylation causes malignant transformation of NIH 3T3 cells.

Abstract: The interferon induced double‐stranded RNA‐activated kinase, PKR, has been suggested to act as a tumor suppressor since expression of a dominant negative mutant of PKR causes malignant transformation. However, the mechanism of transformation has not been elucidated. PKR phosphorylates translation initiation factor eIF‐2 alpha on Ser51, resulting in inhibition of protein synthesis and cell growth arrest. Consequently, it is possible that cell transformation by dominant negative PKR mutants is caused by inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
212
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(223 citation statements)
references
References 47 publications
10
212
1
Order By: Relevance
“…Within this group of genes, we identified the translation initiation factor eIF-4A1 (Eberle et al, 1997), found consistently upregulated at the mRNA level. As the oncogenic potential of other translation initiation factors (e.g., eIF-4E and eIF-2, had already been described in other cells; Lazaris-Karatzas et al, 1990;Donze et al, 1995), we suggested that eIF-4A1 upregulation may contribute specifically to the malignant phenotype of melanoma. In the present paper, we addressed the question whether we can confer inhibitory effects on melanoma cells by obstructing eIF-4A1 gene expression using transient and stable transfection of antisense constructs against eIF-4A1.…”
supporting
confidence: 52%
“…Within this group of genes, we identified the translation initiation factor eIF-4A1 (Eberle et al, 1997), found consistently upregulated at the mRNA level. As the oncogenic potential of other translation initiation factors (e.g., eIF-4E and eIF-2, had already been described in other cells; Lazaris-Karatzas et al, 1990;Donze et al, 1995), we suggested that eIF-4A1 upregulation may contribute specifically to the malignant phenotype of melanoma. In the present paper, we addressed the question whether we can confer inhibitory effects on melanoma cells by obstructing eIF-4A1 gene expression using transient and stable transfection of antisense constructs against eIF-4A1.…”
supporting
confidence: 52%
“…Transformation could be driven in part by a deregulation of protein synthesis initiation since mutant forms of eIF2a, a PKR substrate, are also transforming oncogenes in this assay (Donze et al, 1995). Since dominant negative mutants of PKR also inactivate its activities as a signal transducer, other mechanisms of transformation can be envisaged including a failure to maintain the homeostasis and inhibition of apoptosis.…”
Section: Pkr and P38 Mapkmentioning
confidence: 99%
“…Although previous work has determined that PKR is not essential for translational repression during the UPR (Harding et al, 1999), these experiments were not performed in a PERK null background. Because mice harboring deletion of both PERK and PKR are not currently available, we used a documented PKR dominant negative allele (Donze et al, 1995) to assess its contribution to the regulation of cyclin D1 translation after UPR activation. PERKϪ/Ϫ cells were transiently transfected with an empty vector or a plasmid encoding a dominant negative PKR (K296D) and subsequently treated with tunicamycin.…”
Section: Functional Cooperativity Among Eif2␣ Kinasesmentioning
confidence: 99%